Communication—An Intense Broadband Sensitized Near-Infrared Emitting GdAl3(BO3)4:Ce3+, Yb3+ Phosphor. (9th March 2019) - Zhang, Qiuhong; Ni, Haiyong; Lin, Litian; Ding, Jianming; Ding, Jianhong; Li, Xubo
Abstract : The GdAl3 (BO3 )4 :Ce 3+, Yb 3+ (GAB:Ce 3+, Yb 3+ ) phosphor was developed as a potential solar spectral convertor for crystalline silicon (c-Si) solar cells. The excitation spectra, emission spectra and the possibility of being used as a solar spectral cnvertor of GAB:Ce 3+, Yb 3+ phosphor was investigated. The results show that the GAB:Ce 3+, Yb 3+ phosphor has broadband absorption in the 260–350 nm range which can efficiently facilitate the ultraviolet (UV) light part of the solar spectrum. Furthermore, it can give an intense emission around 975 nm via an energy transfer from Ce 3+ to Yb 3+, matching well with the optimal spectral response of c-Si solar cells.